Fire effects on the composition of Pinus halepensis and Quercus rotundifolia communities in the Bou-Taleb Forest, Algeria, with application of a multivariable analysis - Madoui, Amar; Goldammer, Johann G (Forest Ecology and Management, 2006)
The effect of forest ﬁre on the ﬂora of Bou-Taleb’s forest was studied using a Factorial Correspondence Analysis (FCA). This analysis, implemented by using the Braun-Blanquet method, was applied on ﬂoristic releves investigated on Aleppo pine (Pinus halepensis) and on Holm oak (Quercus rotundifolia) communities which burned at different dates. Other ones represent the non-burnt communities and were used as control. Two analyses were used with all releves (160) and all the species which f > 1 (323). The ﬁrst analysis is applied with a presence-absence coefﬁcient and the second one with an abundance-dominance coefﬁcient. The third analysis involved only releves of burned communities (98) and all species (361). The results of all analyses show the time elapsed since ﬁre (ﬂoristic age) is a discrimination factor. We found a clear separation of young communities on the one side, which appeared immediately after ﬁre, and older communities on the other side. Also, ﬁre effects were linked to the type of communities. There is a distinct difference between Aleppo pine and Holm oak communities. There is invasion of therophytes on the parcels recently burned. Few years after ﬁre, the ﬂoristic composition and structure of communities will be the same as on unburned sites.
Keywords: Aleppo pine; Algeria; FCA; Forest ﬁres; Holm oak; Pinus halepensis; Quercus rotundifolia